PENGARUH LATIHAN REACTIVE JUMP OVER HURDLES TERHADAP DAYA LEDAK (EXPLOSIVE POWER) OTOT TUNGKAI PADA TIM BOLA VOLI PUTRA SMK LABOR BINAAN FKIP UNRI - Nasri '; Slamet '; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem with this research it still a lack of explosive power of leg muscle when they smash and block in SMK Labor Binaan FKIP UNRI man volleyball team.based on the researchers training provide Reactive Jump Over Hurdles. The study aims to find out whether there is effect Reactive Jump Over Hurdles exercises to the leg muscle of explosive power of SMK Labor Binaan FKIP UNRI man volleyball team, so that when a jump smash and block to get the maximum lea. Forms of this research is the experimental treatment (Experimental), with a population of man volleyball players SMK Labor Binaan FKIP UNRI, the data in this research is the entire population of 10 people. The instruments used in this research is to test Vertical Jump, which aims to measure the explosive power leg muscle. After that, the data is processed with statistical, normality test with lilifors test at significance level α (0.05). The hypothesis is the effect Reactive Jump Over Hurdles exercises to the explosive muscle power. Based on the analysis of statistical data, there are an average Pree-test of 48,3 and an average post-test 51,3, then the data is normal with an increase of 3,0. Based on t test analysis produces Ttabel Thitung of 7,69 and 1,833, meaning Thitung> Ttabel. Thus, there Effect of Exercise Reactive Jump Over Hurdles on Explosive Power on a Limb Muscle SMK Labor Binaan FKIP UNRI Man Volleyball TeamKeywords : Reactive Jump Over Hurdles, the explosive muscle power.